PENGARUH TRANSFORMATIONAL LEADERSHIP DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MEDIASI (STUDI KASUS PADA PT BLUE BIRD,TBK) - Dhea Tri Adiningsih (2023)
This research aims to determine the effect of transformational leadership and work motivation on employee performance with commitment organization as a mediating variable for employees at PT Blue Bird, Tbk. This research is a quantitative method with 120 employees of PT Blue Bird, Tbk as samples. This research uses Structural Equation Model (SEM) and data analysis process using SmartPLS version 4.0 as measurement tool. The results of the test obtained (1) there is an influence between transformational leadership on performance, (2) there is an influence between work motivation and performance, (3) exists the influence of organizational commitment on performance, (4) there is an influence between transformational leadership on performance and commitment organization as a mediating variable, (5) there is an influence between work motivation on performance and commitment organization as a mediating variable.